Integration of microfluidic LC with HRMS for the analysis of analytes in biofluids: past, present and future. (June 2015) - Rainville, Paul D; Langridge, James I; Wrona, Mark D; Wilson, Ian D; Plumb, Robert S
Capillary LC (cLC) coupled to MS has the potential to improve detection limits, address limited sample volumes and allow multiple analyses from one sample. This is particularly attractive in areas where ultrahigh assay sensitivity, low limits of detection and small sample volumes are becoming commonplace. However, implementation of cLC–MS in the bioanalytical–drug metabolism area had been hampered by the lack of commercial instrumentation and the need for experts to operate the system. Recent advances in microfabricated devices such as chip-cube and ion-key technologies offer the potential for true implementation of cLC in the modern laboratory including the benefits of the combination of this type of separation with high-resolution MS.